Literasi Media dan Pendidikan Demokrasi Dalam Masyarakat Informasi - Luh Suryatni (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2019)
The importance of media literacy and democratic education for Indonesia society is not only related to the high media exposure or the tsunami of information from the media itself, but also relates to several factors. The first factor is the important role of information in the democratic process. Second is the important role of cultural and citizenship participation, then the third factor is the development of popular culture which made more children and adolescents access digital media in higher frequency. The purpose of writing this paper is to discuss how media literacy and democratic education in the information society to be more intelligent, critical, and wise in choosing information. The data collection method used is a literature study with descriptive analysis techniques. The results of the discussion show that media literacy and democratic education can be a compass for information society to be more intelligent, critical, and wise in choosing information so that they are not trapped in a tsunami of information from the media or become victims of fake facts (hoax) and fake news that can impact the life in society, nation and state.